2015
DOI: 10.1371/journal.pone.0140278
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biological Behavior of In Vitro Human Gingival Fibroblasts on Cold Plasma-Treated Zirconia

Abstract: ObjectiveTo evaluate whether atmospheric-pressure dielectric-barrier-discharge plasma treatment of zirconia enhances its biocompatibility with human gingival fibroblasts.Materials and MethodsThe zirconia disks were divided into four groups and treated using helium atmospheric-pressure dielectric-barrier-discharge plasmas for 30, 60 or 90 s or left untreated. The surface morphology, wettability and chemical elements were analyzed. Fibroblasts density, morphology, morphometry and attachment-related genes express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 47 publications
(62 reference statements)
1
25
0
Order By: Relevance
“…Cell behavior is influenced by this adsorbed layer [ 59 ]. Therefore, it is entirely possible that the unpolished control surface bound the culture medium proteins in a fashion that influenced the cells to initially preferentially increase FAK Y397 phosphorylation at 24 h. At 48 h, FAK phosphorylation was lower compared to 24 h and showed no differences between any groups, so any early advantage to the cells attaching to the control surface may have been transitory, which is in line with past research [ 18 , 60 ]. Also, at 48 h the cells were likely less migratory and more proliferative, which would correlate with decreased FA formation [ 61 ].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Cell behavior is influenced by this adsorbed layer [ 59 ]. Therefore, it is entirely possible that the unpolished control surface bound the culture medium proteins in a fashion that influenced the cells to initially preferentially increase FAK Y397 phosphorylation at 24 h. At 48 h, FAK phosphorylation was lower compared to 24 h and showed no differences between any groups, so any early advantage to the cells attaching to the control surface may have been transitory, which is in line with past research [ 18 , 60 ]. Also, at 48 h the cells were likely less migratory and more proliferative, which would correlate with decreased FA formation [ 61 ].…”
Section: Discussionsupporting
confidence: 84%
“…Previous work, and the work presented herein, suggests that other factors besides surface topography, as measured by R a , may be affecting cellular responses. For example, other groups have shown that surface energy [ 18 ], chemical composition of the surface [ 65 ], and surface features not directly quantifiable by R a affect cellular behavior [ 66 ]. For example, hydroxyl group presence on surfaces has been shown to promote influence integrin binding and so FA formation [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to now, no development of microorganisms resistant to the plasma's cytotoxicity was observed. Plasmas also improve bio‐active surfaces and thus increase the tissue‐compatibility of implant materials . Moreover, plasmas induce metabolic modification in microorganisms which may be useful to improve biodegradation or to increase the production of specific metabolites .…”
Section: Introductionmentioning
confidence: 99%